“Difficult Targets” and Remote Focused Interviews: A Methodological Assessment of Anti-vaxxers - Faggiano, Maria Paola; Mauceri, Sergio; Sonzogni, Barbara; Dentale, Maria; Barbanera, Lorenzo (Italian Sociological Review, 2024)
This proposal wishes to discuss the main results of a qualitative investigation focalized on the theme of vaccine hesitancy, tackled on the basis of a large number of “remotely” conducted focused interviews. This work’s primary objective is that of carrying out a methodological evaluation through which the strengths and weaknesses of the investigation tools employed may be clarified, in consideration of both the reference participants, as well as the online transposition of interactions which are traditionally actualized in person. The focused interviews represent the empirical base from which multiple and significant methodological observations became achievable. The online context in which they took place had a positive impact on the established ambience, it broadened its geographical reach, and fruitfully affected the fidelity of the collected information. As a preview of some of the surfaced insights, some of the advantages include: many of the participants reached expressed their opinion on the vaccination campaign in a particularly spontaneous, uninhibited and truthful manner; they dwelled on the conduct adopted during the pandemic, as well as on attitudes and emotional states attributable to dimensions like contagion, civic responsibility towards those close to them, the social consequences of refusing the vaccine, their relationship with the traditional science of medicine and the establishment by and large. Equally complex is the spectrum of disadvantages, among which are the lack of consent by some subjects to audio-video recording of the interview, the pronounced reluctance to discuss personal problems on part of those participants less accustomed to the use of digital devices, or those who appeared to be visibly uncomfortable before a screen.